2020
DOI: 10.15282/ijame.17.1.2020.05.0560
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Welding Parameter on Mechanical Properties and Macrostructure of AA1100 Using Autogenous Tig Welding

Abstract: In this paper, an autogenous tungsten inert gas (TIG) welding was performed to understand the characteristic effect of butt joint weld on AA1100 under various parameters. The effect of TIG current and welding speed was selected to study the mechanical properties, porosity, and macrostructure of the weld metal (WM). Based on experimental results, the top bead width (TBW) will increase directly proportional to the increased of welding current. Furthermore, welding current and welding speed affected the strength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
5
0
2
Order By: Relevance
“…Parameter yang harus diperhatikan pada GMAW antara lain kuat arus, voltase busur, dan kecepatan pengelasan. Kuat arus pada las GMAW akan berpengaruh besar pada kapasitas pencairan, ukuran dan geometri manik las, dan kedalaman penetrasi [9]. Makin tinggi arus listrik pengelasan, makin tinggi pula penembusan atau penetrasi serta kecepatan pencairan.…”
Section: Pendahuluanunclassified
“…Parameter yang harus diperhatikan pada GMAW antara lain kuat arus, voltase busur, dan kecepatan pengelasan. Kuat arus pada las GMAW akan berpengaruh besar pada kapasitas pencairan, ukuran dan geometri manik las, dan kedalaman penetrasi [9]. Makin tinggi arus listrik pengelasan, makin tinggi pula penembusan atau penetrasi serta kecepatan pencairan.…”
Section: Pendahuluanunclassified
“…Use of flux helps to refine the microstructure properties at HAZ with low as well as high heat input [2,3]. Baskoro et al [4] investigated the effect of parameter of welding on microstructure and mechanical properties of AA1100 using autogenous TIG welding. They concluded that weld width increases with increase in welding current.…”
Section: Introductionmentioning
confidence: 99%
“…The recent development of the manufacturing process requires high awareness of environmental and health problems [1], [2]. It is required that a process should be clean, less polluting, minimize the use of natural resources, reducing social and health impacts [3,4].…”
Section: Introductionmentioning
confidence: 99%